Internet addiction syndrome (IAS) and personality - Jakubik, Andrzej; Popławska, Justyna (Studia Psychologica: Theoria et praxis, 2003)
The work is empirical in character and concerns findings in the relationship between Internet addiction syndrome and personality (IAS). It was found thatIAS is linked to some personality traits. But the results only suggest – becausethere was no significant statistical verification of the hypothesis – that Internetaddiction syndrome probability may be determined by specific personalityfactors.